Peran KUA dalam Meminimalisir Pernikahan di Bawah Tangan - Sukur, Abd. (Journal of Islamic and Social Studies, 2023)
In Indonesia, marriage is considered valid if it is carried out according to the respective religious laws as stated in chapter 2 of Law number 1 of 1974, which contents marriages are carried out according to their respective beliefs/religions and every marriage must be registered according to the law apply. However, there are still many Indonesian people who do marriages, not following what has been stipulated in the law, such as underhand marriages or known as sirri marriages. The purpose of this research is to describe the role of KUA in efforts to minimize the occurrence of underhand marriage in the Mojo sub-district. In this study the method used is a type of qualitative descriptive research method. Collection techniques are carried out by observation, interviews, documentation. The data in this study, in the form of data from interviews, and written data at the KUA. The results of this study show the three main roles of the KUA in efforts to minimize the occurrence of underhand marriages, first, providing socialization to the public about the importance of registering marriages; Second, conducting counseling on marriage and happy family registration at the Office of Religious Affairs (KUA) for prospective brides and guardians; third, cooperating between the religious affairs office and village apparatus to conduct outreach to the community.